Genetic analysis of morphological traits in a new, versatile, rapid-cycling Brassica rapa recombinant inbred line population - Bagheri, Hedayat; El-Soda, Mohamed; van Oorschot, Inge; Hanhart, Corrie; Bonnema, Guusje; Jansen - van den Bosch, Tanja; Mank, Rolf; Keurentjes, Joost; Meng, Lin; Wu, Jian; Koornneef, Maarten; Aarts, Mark G. (Frontiers in Plant Science, 2012)
A recombinant inbred line (RIL) population was produced based on a wide cross between the rapid-cycling and self-compatible genotypes L58, a Caixin vegetable type, and R-o-18, a yellow sarson oil type. A linkage map based on 160 F7 lines was constructed using 100 SNP, 130 AFLP®, 27 InDel and 13 publicly available SSR markers. The map covers a total length of 1150 cM with an average resolution of 4.3 cM/marker. To demonstrate the versatility of this new population, 17 traits, related to plant architecture and seed characteristics, were subjected to QTL analysis. A total of 47 QTLs were detected, each explaining between 6 to 54% of the total phenotypic variance for the concerned trait. The genetic analysis shows that this population is a useful new tool for analyzing genetic variation for interesting traits in B. rapa, and for further exploitation of the recent availability of the B. rapa whole genome sequence for gene cloning and gene function analysis.